1991
DOI: 10.1080/00224545.1991.9713881
|View full text |Cite
|
Sign up to set email alerts
|

Death Anxiety in Japan and Australia

Abstract: This study compared death anxiety ratings as measured by the Templer Death Anxiety Scale (Templer, 1970) in 121 Japanese and 139 Australian subjects. Japanese subjects had significantly higher death anxiety scores than their Australian counterparts. Australian women scored significantly higher than Australian men, but no sex differences were found in the Japanese sample. A slight but statistically significant positive correlation was found between age and death anxiety scores. This study contradicted other res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 19 publications
5
46
1
2
Order By: Relevance
“…Unexpectedly, however, those living with family members actually reported more death anxiety than those living alone. The increased death anxiety in the elderly is consistent with some previous results in U.S. (Neimeyer et al, 1988;Thorson & Powell, 1994) and one Pakistani sample (Kausar & Saima, 2002), but not other research in U.S. samples (McMordie & Kumar, 1984;Schumaker et al, 1991). Given the relative older age of the present sample compared with others, an implication is that death anxiety increases with age in those over 70 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…Unexpectedly, however, those living with family members actually reported more death anxiety than those living alone. The increased death anxiety in the elderly is consistent with some previous results in U.S. (Neimeyer et al, 1988;Thorson & Powell, 1994) and one Pakistani sample (Kausar & Saima, 2002), but not other research in U.S. samples (McMordie & Kumar, 1984;Schumaker et al, 1991). Given the relative older age of the present sample compared with others, an implication is that death anxiety increases with age in those over 70 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…Pettinati, Horne, and Staats (1985) found that bulimics and, to a lesser extent, anorectics scored high on standard tests of hypnotic susceptibility. This is consistent with the view that an extreme drive for thinness is an unquestioning over-acceptance of the all-pervasive culture-based suggestion to "be thin" (Schumaker & Groth-Marnat, 1988).…”
Section: Please Scroll Down For Articlesupporting
confidence: 88%
“…It could be speculated that different aspects of hypnotizability might relate to both the etiology and maintenance of extreme attitudes towards eating and weight regulation. Waking suggestibility might be a factor in the transmission of shared beliefs ("be thin") within a person's family and culture (Schumaker & Groth-Marnat, 1988;Swartz, 1985), and the dissociative aspect of hypnotizability might relate to the perceptual distortions and dissociative phenomenon frequently reported in populations with extreme concern with food regulation (Bliss, 1982(Bliss, , 1983Kaffman & Sadeh, 1989). In particular, the family is likely to be a significant factor in the formation of attitudes towards eating and weight regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Schumaker, Warren, and Groth-Marnat (1991) found higher death anxiety among Japanese males compared to Australian males, suggesting fewer defensive postures toward death among Japanese males. Women may also have different sociocultural experiences and cultural conditioning than men.…”
Section: Attributes Of Death Anxietymentioning
confidence: 80%